Correlation Cholesterol and Triglyceride Level on Cognitive Function in Type 2 Diabetes Mellitus - Iin novita Nurhidayati Mahmuda; Fairuz Ulfah (Universitas 'Aisyiyah Yogyakarta, 2021)
Diabetes Mellitus (DM) is a type of non-communicable disease that is still a public health problem both globally, regionally, nationally and locally. The prevalence of DM in the world is 1.9% and makes DM the seventh cause of death in the world. One of the complications caused by DM is a decrease in cognitive function. The triggers for cognitive function include high cholesterol and triglyceride levels. The purpose of this study was to determine the correlation between cholesterol and triglyceride leves on cognitive function in Type 2 Diabetes Mellitus at Boyolali. This study is an analytic observational study with a cross sectional approach .The subject are 51 respondents. The sampling technique used in this study was purposive sampling technique. Data analyzed with chi-square test . it was found that there was a correlation between cholesterol level and cognitive function with a p-value of 0.003 0.05 and there was also correlation triglyceride level and cognitive function with a p-value of 0.000 0.05. There is a significant correlation between cholesterol and triglyseride level with cognitive function in type II diabetic patient.